THE SEMI-CLASSICAL SOLUTION FOR A CLASS OF SEMILINEAR INITIAL VALUE CONTROL PROBLEMS IN BANACH SPACE - Salah, Manaf Adnan (Al-Nahrain Journal of Science, 2010)
In this paper, the local existence and uniqueness of S-classical solution of a class of semilinearinitial value control problems which defined as:0d z t g t z t Az t f t z t B t t 0dtz 0 zw w w ww  ,    ,  w , have been discussed and proved in suitable Banach spaces. All results are obtained by using Banachcontraction principle and depending on the theory of analytic semigroup of control problems Keywords: S-classical solution,control problem in infinite dimensional spaces,fixed point theorem and y